Combined sorption/transport of sodium dodecyl sulfate and hydrochloric acid in a blend of cellulose acetate butyrate with cellulose acetate hydrogen phthalate - Valente, Artur J. M. (2004)
The transport of hydrochloric acid (0.001-0.1 M) and sodium dodecyl sulfate (0.001-0.1 M) has been measured through a membrane consisting of a blend of cellulose acetate butyrate and cellulose acetate hydrogen phthalate. The cellulose derivative blend is suggested to suffer an alteration in the degree of hydrophobicity when in equilibrium with sodium dodecyl sulfate (SDS) through hemimicelle formation. An increase in surface hydrophobicity of the blend when in equilibrium with SDS solution was observed by fluorescence measurements using the vibronic bands of the probe pyrene, as well as by water desorption kinetics; a decrease of the effective diffusion coefficients from 1.2 × 10-11 m2 s-1 in the absence of SDS to approximately 2 × 10-13 m2 s-1 in its presence was found. The value obtained for the mutual diffusion coefficient of HCl in the concentration range 0.001-0.1 M (D=4.2×10-14 m2 s-1) shows also that the membrane presents hydrophobic features. The flux of SDS in the blend membrane at different pH values shows two distinct permeation rates depending on the cmc. However, from the calculation of permeability coefficients at SDS concentrations below the cmc a clear decrease in P is found, whilst, at concentrations above the cmc the permeability coefficients are nearly constant, only showing a slightly increase. The diffusion coefficients of SDS in the blend increase over the whole SDS concentration range analysed and show an effective diffusion coefficient 2-3 orders of magnitude below the diffusion coefficients of SDS in aqueous solutions. This fact suggests that the only diffusing species are SDS unimers. The presence of HCl in the SDS bulk solution has the effect of increasing the permeability and diffusion coefficients. Mutual analysis of permeation and diffusion coefficients and sorption isotherms shows that, on decreasing the pH, the interactions between SDS and the polymer network decrease. This is also reflected in a clear decrease of the hydrophobic interactions between the diffusing and polymeric species, provoked by a decrease in the unimer-unimer association.